Երկու հնատիպ հմայիլների ուսումնասիրության հետքերով - Գրիգորյան, Սաթենիկ
Two recently discovered printed scroll amulets dated to the 18th century are preserved in Vardadzor village (Martuni region) by separate families who moved to the region from Alashkert, region of Western Armenia in the years 1829-1830. The older amulet (printed in 1716), called the “Amulet of Andreas” — belongs to the family of Artashes Grigoryan, a resident of Varadzor. The colophons of the scroll contain noteworthy information concerning the owners of the amulets. The other Amulet (printed in 1717) belongs the family of Aleksan Sirakanyan, also residents of Vardadzor. The Amulets feature 33 prayers and engraved images. This discovery is of great significance to the study of Armenian talismans from the early modern period. В двух семьях, переелившихся в село Вардадзор (Мартунинский район) из Алашкертской области Западной Армении (1829-1830-е гг.), находятся старопечатные свитки-обереги (амулеты) XVIII века. Первый по времени (1716 г.), «Свиток-оберег Андрея», принадлежит семье Арташеса Григоряна, жителю села Вардадзор. На одном из этих свитков имеются памятные записи, содержащие примечательную информацию. Второй свиток (1717 г.) принадле- жит жителям того же села, семье Алексана Сираканяна. Оба оберега по сей день хранятся в селе. Они богаты молитвами и гравюрами, число которых в первом из них достигает 33-х. Таким образом, список известных экземпляров армянских старопечатных свитков-оберегов пополнился ещё двумя нововыявленными единицами.
Keywords: Մատենագիտություն; Օկուլտականություն